The effect of the development and restoration projects on the culture of Marsh Arabs - Ramadan, Habiba (AUC Knowledge Fountain, 2017)
In 1991, the Marsh Arabs of Iraq revolted against the government of Saddam Hussein. Hussein responded by undertaking self-declared development projects in the Marshlands, draining the region of water. Without the ability to practice traditional economic and social activities, which relied on their proximate environment, the majority of the Marsh Arab community was displaced. The project resulted in the desertification of an area nearly the size of the Aral Sea, what archeologists have described as environmental genocide. In 2003, the US government embarked on a restoration program to divert water back to the marshlands and improve the available social services in marsh region. The project has succeeded in restoring a significant proportion of the marshes. However, large numbers of the Marsh Arabs have not returned to the land, calling into question such a project’s ability to achieve more than environmental regeneration. This thesis examines the effects of environmental destruction and restoration on a community and its culture, using the Marsh Arabs as a case study. It asks whether the US-led environmental restoration program has restored the Marsh Arabs’ culture. This thesis argues that the Hussein’s development project led to cultural loss that was not rectified by the American restoration program. In making this argument the thesis examines changes in: a) the economic activities, daily tasks and routines of the Marsh Arabs; and b) the transmission of traditional ecological knowledge (TEK) to younger generations.